2016
DOI: 10.1155/2016/3857579
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Inferior Conjunctival Fornix in Contracted Socket and Anophthalmic Socket Syndrome: A Novel Technique to Deepen the Fornix Using Fascia Lata Strips

Abstract: Purpose. To evaluate a new surgical technique using fascia lata to deepen the shallow inferior conjunctival fornix in contracted socket and anophthalmic socket syndrome. Methods. A prospective controlled study in which 24 sockets of 24 patients who were unable to wear and retain their ocular prosthesis due to shallow inferior fornix were enrolled and categorized into anophthalmic socket syndromes (9 patients) and contracted sockets (15 patients). Another 24 patients who underwent evisceration or enucleation wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…No expensive consumables were required for this procedure and required less surgical time along with absence of an additional donor site since silicone tubes are widely available. This modified technique had a 96% success rate with minimal risk of complication; whereas other studies reported a 93.3% success rate with fascia lata strips 10 , 83.33% success rate with amniotic membrane grafts 8 and 77.3% with oral mucosal grafts 9 . Since, the silicone bolsters are placed within the fornix, they are cosmetically acceptable for the patient as well.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…No expensive consumables were required for this procedure and required less surgical time along with absence of an additional donor site since silicone tubes are widely available. This modified technique had a 96% success rate with minimal risk of complication; whereas other studies reported a 93.3% success rate with fascia lata strips 10 , 83.33% success rate with amniotic membrane grafts 8 and 77.3% with oral mucosal grafts 9 . Since, the silicone bolsters are placed within the fornix, they are cosmetically acceptable for the patient as well.…”
Section: Discussionmentioning
confidence: 83%
“…8,16 Fascia lata strips have also been used to deepen the shallow inferior fornix in anophthalmic sockets but necessitates a donor site and has risk of complications. 10 The eventual aim of management is to allow the ocular prosthesis to stay in place and resemble the fellow eye as much as possible as an improper fitting prosthesis can be psychologically disturbing for an individual. 3 A modified surgical technique was performed in the present study by applying 3 sutures from within the fornix centrally, medially and laterally, full thickness through the lower eyelid taking the inferior orbital rim periosteum in the suture bite together with closure of the fornix sutures with silicone tube bolsters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diese narbigen Veränderungen können u. a. durch Verkürzung und Schrumpfung der konjunktivalen Fornices das Einsetzen einer Prothese unmöglich machen [61]. Die Prothesenfähigkeit kann dann nur durch eine chirurgische Intervention wiederhergestellt werden [62].…”
Section: Komplikationen Des Prothesentragensunclassified
“…Standard procedures for fornix reconstruction include fornix-deepening sutures with or without the use of buccal mucosal transplant. 1 A dermis fat graft (DFG) may also be used to increase the lining of the socket. In a subset of patients these standard procedures unfortunately fail, and severe recurrent contraction of the socket results in the inability to wear any ocular prosthesis.…”
Section: Introductionmentioning
confidence: 99%